SISTEM INFORMASI QR KAKAO SEBAGAI MEDIA INFORMASI MANAJEMEN HASIL TANI KAKAO DI DESA SAJAU, BULUNGAN BERSAMA PT PKN - Yehezkiel; Falaah Abdussalaam (POLITEKNIK PIKSI GANESHA, 2025)
Cocoa farming in Bulungan Regency, particularly in Sajau Village, plays a vital role in supporting the rural economy. However, the management of harvest data still faces challenges, especially due to manual record-keeping, which tends to be inefficient. This study aims to develop a QR Code–based information system called QR Kakao that assists farmers and facilitators in managing and accessing harvest data more quickly, accurately, and in a structured manner. The research employed a qualitative approach through field observations, interviews with farmers and stakeholders, and literature studies. Meanwhile, the software development process adopted the Waterfall model, consisting of requirement analysis, system design, implementation using the Laravel framework, testing, development, and maintenance. The QR Kakao system successfully provides core features such as generating and scanning QR Codes containing information such as farmer identity, farm location, harvest dates, and harvest yield. The implementation of this system offers several benefits, including easier access to harvest information, improved efficiency in data management, and encouragement of digitalization within smallholder cocoa farming. With the support of PT Pesona Khatulistiwa Nusantara, QR Kakao is expected to contribute to a more modern, transparent, and sustainable cocoa farming management system in Sajau Village.